Seismic Performance and Damage Evaluation of Reinforced Concrete Structures Based on Field Investigation Made After February 6, 2023, Kahramanmaraş Earthquakes - Sevim, B.; Ayvaz, Y.; Akbulut, S.; Aydiner, M. F.; Uzun, S.; Ari, A. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2024)
On 6 February 2023, an earthquake doublet occurred, the first at Kahramanmaras Pazarcik district (Mw=7.7) at local time 04:17 and the second, which approximately 9 hours after the first earthquake, occurred at Kahramanmaras Elbistan district (Mw=7.6) at local time 13:24 in Turkiye. It is a disaster affected 11 cities in the eastern region in Turkiye and is referred as Disaster of the Century. Earthquake disasters allow humanity to investigate seismic behavior under related construction details and revising the seismic codes.The authors conducted observational research to obtain interpretive information and digital data by investigating structural damages of moderately and heavily damaged buildings from earthquake sites. In this paper, performance evaluation is done based on existence of soft storey, weak column-strong beam, deficiencies and pounding effect. Damages are classified as beam, column, beam-column joint and shear wall, infill wall, roof and scaffolding damages. Ampleness of soft storey, column damages, inadequate joint reinforcement, inadequate structural ductility and low capacity, strong beam-weak column effect, and infill wall damages have been observed from the field. As a result of field observation, structural deficiencies, irregularities and mismatching capacity design principles have been concluded as common problems of reinforced concrete buildings in the Kahramanmaras earthquake site.
Keywords: Field investigation; reinforced concrete; earthquake performance; damage level; Kahramanmaras earthquakes; BUILDINGS; TURKEY; VAN; Geochemistry & Geophysics; Engineering